Use of a corneal impression membrane and PCR for the detection of herpes simplex virus type-1. Issue 9 (29th July 2019) - Brunner, Matthias; Somerville, Tobi; Corless, Caroline E.; Myneni, Jayavani; Rajhbeharrysingh, Tara; Tiew, Stephanie; Neal, Timothy; Kaye, Stephen B.
Abstract : Purpose . To investigate the use of a corneal impression membrane (CIM) for the detection of herpes simplex virus type 1 (HSV-1) in suspected herpes simplex keratitis (HSK). Methodology . In the laboratory study, swabs and CIMs made from polytetrafluoroethylene were spiked with different concentrations of HSV-1. DNA was extracted and real-time PCR undertaken using two sets of primers. In the clinical study, consecutive patients presenting with suspected HSK were included. For each patient, samples were collected from corneal lesions with a swab and a CIM in random order. Clinical details were collected using a standardized clinical form and patients were categorized into probable, presumed and possible HSK. Results . There was no difference in the performance of both primer sets for all HSV-1 dilutions ( P =0.83) using a CIM or between a CIM and a swab ( P =0.18). In total, 110 patients were included. Overall, 73 patients (66.4 %) had probable, 20 patients (18.2 %) presumed and 17 patients (15.5 %) possible HSV-1 keratitis. The HSV-1 detection rate was significantly higher using a CIM (40/110, 36.4 %) than a swab (28/110, 25.5 %) ( P =0.004). In the probable HSV keratitis group, the detection rate using a CIM was 43.8 % compared to 27.4 % for a swab ( P =0.004). The cycle threshold values obtained for the conjunctival swabs were higher than those obtained for the CIMs ( P <0.001). Conclusions . In suspected HSK, a CIM is a useful alternative to a swab and more likely to detect the presence of HSV-1.